2022
DOI: 10.3390/foods11244004
|View full text |Cite
|
Sign up to set email alerts
|

Modified Atmosphere Packaging and 1-Methylcyclopropene Treatments Maintain the Fruit Quality of ‘Wonmi’ Persimmons during Export Simulation

Abstract: Persimmons are one of the most important export fruits in South Korea, where several tons are exported across the globe each year. In this study, the quality attributes of ‘Wonmi’ persimmon fruits were evaluated during an export simulation at 0 °C, 10 °C, and 24 °C with a combination of 1-Methylcyclopropene (1-MCP) and modified atmosphere packaging (MAP) treatments. The relative humidity during the export simulation was greater at room temperature (75–92%) and 0 °C (85% to 93%) than at 10 °C (42% to 60%). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Studies have shown that the color change of fresh products packaged under a high CO 2 and low O 2 atmosphere was delayed due to reduced ethylene synthesis [21][22][23]. The FOLO treatment was the most effective in preserving the color of the bell pepper and maintaining its visual quality compared to other treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the color change of fresh products packaged under a high CO 2 and low O 2 atmosphere was delayed due to reduced ethylene synthesis [21][22][23]. The FOLO treatment was the most effective in preserving the color of the bell pepper and maintaining its visual quality compared to other treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Modified atmosphere packaging (MAP) is a technology used to extend the quality and shelf life of horticultural products of high commercial value [7,20,21]. In recent studies using fruits such as pomegranate [22] and persimmon [23], packaging techniques were used to effectively enhance the postharvest quality and shelf life. The packaging of bell peppers in perforated plastic films has been confirmed to reduce water loss, delay softening, and extend shelf life during storage [3,21].…”
Section: Introductionmentioning
confidence: 99%